2018
DOI: 10.29050/harranziraat.344747
|View full text |Cite
|
Sign up to set email alerts
|

Besi Sığırı Rasyonlarında Tamamlayıcı Yem Olarak Farklı Şekillerde İşlenmiş Arpa ve Mısır Kullanımının Performans, Bazı Biyokimyasal Parametreler ile Serum Laktat ve Bikarbonat Düzeyi Üzerine Etkileri

Abstract: Besi sığırı rasyonlarında tamamlayıcı yem olarak farklı şekillerde işlenmiş arpa ve mısır kullanımının performans, bazı biyokimyasal parametreler ile serum laktat ve bikarbonat düzeyi üzerine etkileri. Harran Tarim ve Gida Bilimleri Dergisi, 22(2): 275-283

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Although, the result of this study for ash content of barley was lower than those of Toprak et al (2018) and Denli and Demirel (2016). The different barley kinds and varieties used in the studies and their production conditions (soil, region, precipitation, climate, fertilization etc.)…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Although, the result of this study for ash content of barley was lower than those of Toprak et al (2018) and Denli and Demirel (2016). The different barley kinds and varieties used in the studies and their production conditions (soil, region, precipitation, climate, fertilization etc.)…”
Section: Discussioncontrasting
confidence: 57%
“…In the earlier studies, the dry matter (Toprak et al 2018, Yahaghi et al 2012, Denli and Demirel 2016, CP and EE (Sevim et al 2017) contents of barley were found about 90%, between 12.60-13.10% and between 1.59-1.80%, respectively. The results of the study for dry matter, CP and EE contents of barley were compatible with the previous studies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation